Endogenous and exogenous domain markers of the rat hepatocyte plasma membrane (The Rockefeller University Press, 1985)
We have used a combined biochemical and morphological approach to establish the suitability of certain endogenous and exogenous domain markers for monitoring the separation of rat hepatocyte plasma membrane domains in sucrose density gradients. As endogenous domain markers, we employed two of the integral plasma membrane protein antigens, HA 4 and CE 9, localized to the bile canalicular and sinusoidal/lateral domains, respectively, of the hepatocyte plasma membrane in rat liver tissue (Hubbard, A. L., J. R. Bartles, and L. T. Braiterman, 1985, J. Cell Biol., 100:1115-1125). We used immunoelectron microscopy with a colloidal gold probe to demonstrate that HA 4 and CE 9 retained their domain-specific localizations on isolated hepatocyte plasma membrane sheets. When the plasma membrane sheets were vesiculated by sonication and the resulting vesicles were centrifuged to equilibrium in sucrose density gradients, quantitative immunoblotting revealed that the vesicles containing HA 4 and those containing CE 9 exhibited distinct density profiles. The density profile for the bile canalicular vesicles (marked by HA 4) was characterized by a single peak at a density of 1.10 g/cm3. The density profile for the sinusoidal/lateral vesicles (marked by CE 9) was bimodal, with a peak in the body of the gradient at a density of 1.14 g/cm3 and a smaller amount in the pellet (density greater than or equal to 1.17 g/cm3). We used this sucrose gradient fractionation as a diagnostic procedure to assign domain localizations for several other hepatocyte plasma membrane antigens and enzyme activities. In addition, we used the technique to demonstrate that 125I- wheat germ agglutinin, introduced during isolated liver perfusion at 4 degrees C, can serve as an exogenous domain marker for the sinusoidal domain of the rat hepatocyte plasma membrane.